Psychological Empowerment and its Impact on Contextual Performance - Abd Hafid, Doaa; Mahdi Saleh , Khaled (Journal of Economics and Administrative Sciences, 2024)
Purpose: The purpose of the research was to determine if psychological empowerment might be regarded as a critical component in raising employees’ contextual performance in the workplace. Or do other elements come into play when defining professional performance? Theoretical framework: The goal of the study was to draw attention to how crucial contextual performance and psychological empowerment are as fundamental management ideas in the area under investigation. Design/methodology/approach: The research used a descriptive methodology, resolution-based tool analysis, tabulation, and analysis using a ready statistical software. (SPSS). The Office of the Shia Endowment/Administrative and Financial Service was chosen by the researcher to represent the Study Community. There were 260 employees in the research sample. To arrive at the study’s conclusions, statistical techniques such as CE, standard deviation, natural distribution test, persistence factor, and F test were used. Findings: By analyzing the effects of psychological empowerment and its dimensions on the contextual performance of the employees of the studied organization, it is possible to demonstrate the connections between them. Research, Practical & Social implications: The need for government agencies to ensure that employees in the research service are required and that there is a fair system of salaries and other allocations in comparison with other ministries so that workers do not feel bad in the workplace. Originality/value: The results indicate that the number of publications is growing, and the management and business area is the one that contributes the most, with the countries that produce in co-authorship also providing the most publications